2014
DOI: 10.1371/journal.pone.0093686
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Serum Lipid Smoothness on the Progression and Vulnerability of Atherosclerotic Plaques in Rabbits

Abstract: ObjectiveWe aimed to explore the effects of lipid smoothness on the progression and vulnerability of atherosclerotic plaques.Approach24 rabbits were divided into three groups randomly. Group 1 was given standard chow diet; group 2 was fed with cholesterol-rich diet; for group 3, subjects were planned to take cholesterol-rich diet at the first phase for 12 weeks and during the second phase, low-fat and cholesterol-rich diet was then applied alternately every three weeks till the end of the experiment. Lipid pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The current study found that the variation rate of non-HDL-C and Lp(a) during the follow-up period was signi cantly correlated with the level of NLR, and they were independent risk factors for NLR, which indicated that non-HDL-C and Lp(a) variability rate can re ect and predict the chronic low-grade in ammation level in patients with CHD after elective PCI. Previous studies have found that compared with the low blood lipid variation rate group, the high blood lipid variation rate group has higher in ammatory cell in ltration around the brous cap of the vascular artery plaque [24], which is consistent with the results of current study, and provides important basic research evidence. Although the mechanism by which the increased variation rate of non-HDL-C and Lp(a) promotes in ammation is still unclear, controlling blood lipid variability can affect NLR level, thereby improving the prognosis of patients undergoing PCI, and has good application value.…”
Section: Discussionsupporting
confidence: 91%
“…The current study found that the variation rate of non-HDL-C and Lp(a) during the follow-up period was signi cantly correlated with the level of NLR, and they were independent risk factors for NLR, which indicated that non-HDL-C and Lp(a) variability rate can re ect and predict the chronic low-grade in ammation level in patients with CHD after elective PCI. Previous studies have found that compared with the low blood lipid variation rate group, the high blood lipid variation rate group has higher in ammatory cell in ltration around the brous cap of the vascular artery plaque [24], which is consistent with the results of current study, and provides important basic research evidence. Although the mechanism by which the increased variation rate of non-HDL-C and Lp(a) promotes in ammation is still unclear, controlling blood lipid variability can affect NLR level, thereby improving the prognosis of patients undergoing PCI, and has good application value.…”
Section: Discussionsupporting
confidence: 91%
“…A study performed in an insulinoma tumor cell line also revealed that both high and low cellular cholesterol contents were inhibitory for insulin secretion [ 21 ]. Another study in rabbits has suggested that lipid fluctuation could accelerate the progression and vulnerability of atherosclerotic plaques through worsening arterial endothelial dysfunction and inflammatory reactions [ 22 ]. In line with the above mentioned studies, recent studies suggest that glycemic variability and visit-to-visit variability in BP could deteriorate pancreatic insulin secretory function and increase cardiovascular risk [ 23 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This investigation emphasizes non-HDL-C as a comprehensive measure of lipid metabolism characteristics, revealing the correlation between atherogenic cholesterol and inflammatory status. We discovered a significant correlation between the variability of non-HDL-C and the level of NLR, suggesting non-HDL-C variability as an independent predictor of chronic inflammatory status in post-PCI CHD individuals ( 21 ).…”
Section: Discussionmentioning
confidence: 92%